Intertextuality of Personosphere as a Factor of Genre Metamorphicality: Clifford Simak's Novel "Shakespeare's Planet" - Paranyuk Dan, Tychinina Aliona (Stefan Cel Mare University, 2019)
The article deals with the issue of intertextual potential of the personosphere of Clifford Simak’s novel Shakespeare’s Planet, as well as investigates its generative function in the process of gender-making (from science fiction to a crossover of a fantasy type). This gender’s metamorphicality is ensured by a creative significance of a confocal character, which is presented in the text by William Shakespeare. The personosphere of the text understudies rests on the opposition “mine-thine”, which forms twin dichotomous rings. The authors of the article conclude that the intertextual image of Shakespeare is of a reincarnational nature, being eventually implemented in the simulacrum of the proto-text.
Keywords: intertextuality of personosphere; gender metamorphicality; William Shakespeare; Clifford Simak